Psychosocial functioning following moderate-to-severe pediatric traumatic brain injury: recommended outcome instruments for research and remediation studies. Issue 5 (27th May 2020) - Wearne, Travis; Anderson, Vicki; Catroppa, Cathy; Morgan, Angela; Ponsford, Jennie; Tate, Robyn; Ownsworth, Tamara; Togher, Leanne; Fleming, Jennifer; Douglas, Jacinta; Docking, Kimberley; Sigmundsdottir, Linda; et al.
ABSTRACT: Psychosocial functioning is compromised following pediatric traumatic brain injury (TBI), with the past few decades witnessing a proliferation of research examining the effect of childhood brain insult on a range of psychosocial outcomes. This paper describes the systematic recommendation of outcome instruments to address psychosocial functioning following pediatric TBI. A total of 65 instruments across 11 psychosocial areas (i.e., Global Outcome, Communication, Social Cognition, Behavioural and Executive Function, Other Neuropsychological Functioning, Psychological Status, TBI-related Symptoms, Activities and Participation, Support and Relationships, Sense of Self, and Health-Related Quality of Life) were reviewed using various assessment methods, including working groups, literature searches, comparisons with selection guidelines, and international expert opinion. Each measure was reviewed for its usefulness across early recovery, intervention, and outcome related studies. 34 instruments were recommended and classified according to the World Health Organization's International Classification of Functioning, Disability and Health taxonomy and categorised by psychosocial area. This compilation provides a common framework to guide the activities of clinicians and researchers in psychosocial rehabilitation. It is anticipated that these will foster a multidisciplinary approach to psychosocial dysfunction to enhance the evaluation, prediction, and improvement of functional outcomes for those with pediatric TBI.